2011
DOI: 10.1111/j.1365-2966.2011.19357.x
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku observation of the Galactic supernova remnant CTB 37A (G348.5+0.1)

Abstract: We present here the results of the observation of CTB 37A obtained with the Xray Imaging Spectrometer onboard the Suzaku satellite. The X-ray spectrum of CTB 37A is well fitted by two components, a single-temperature ionization equilibrium component (VMEKAL) with solar abundances, an electron temperature of kT e ∼ 0.6 keV, absorbing column density of N H ∼ 3 × 10 22 cm −2 and a power-law component with photon index of Γ ∼ 1.6. The X-ray spectrum of CTB 37A is characterized by clearly detected K-shell emission … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
6
23
0
Order By: Relevance
“…The age of the SNR shell is estimated around 1300 yr , which is consistent with the age between 750 and 2100 yr estimated by Kumar et al (2014). Kes 73 has been also observed by ROSAT (Helfand et al 1994), ASCA , Chandra (Lopez et al 2011) and Suzaku (Sezer et al 2010).…”
Section: Kes 73supporting
confidence: 86%
“…The age of the SNR shell is estimated around 1300 yr , which is consistent with the age between 750 and 2100 yr estimated by Kumar et al (2014). Kes 73 has been also observed by ROSAT (Helfand et al 1994), ASCA , Chandra (Lopez et al 2011) and Suzaku (Sezer et al 2010).…”
Section: Kes 73supporting
confidence: 86%
“…Using Chandra and XMM-Newton observations, Aharonian et al (2008a) found diffusive thermal X-ray emission from the east part of the remnant and derived a flux upper limit of -3.5 10 13 erg cm −2 s −1 for nonthermal emission in the 1-10 keV range. Sezer et al (2011) suggested that the diffuse thermal X-ray emission of CTB 37A is produced by shocked interstellar/circumstellar medium and estimated an ambient gas density of~-f 1 1 2 cm −3 and an age of~´f 3 10 4 1 2 years, where f is the volume filling factor of the emitting plasma. Assuming a distance of 11.3 kpc, Pannuti et al (2014) obtained similar results with an electron density n e =0.77 cm −3 and an age of3.2 4.2 10 4 ( -) years by analyzing the X-ray spectrum.…”
Section: Ctb 37amentioning
confidence: 99%
“… References. (1) Paper I; (2) Velázquez et al (2002); (3) Green (2009); (4) Tian et al (2007); (5) Abdo et al (2010a); (6) Seta et al (1998); (7) Brogan & Troland (2001); (8) Koo et al (2005); (9) Koo & Moon (1997a); (10) Green (1990); (11) Blair, Sankrit & Raymond (2005); (12) Miyata et al (1994); (13) Sezer et al (2011); (14) Reynoso & Mangum (2000); (15) Slane et al (2002). …”
Section: Application To Individual Snrsmentioning
confidence: 99%